2019
DOI: 10.1139/bcb-2018-0313
|View full text |Cite
|
Sign up to set email alerts
|

The long noncoding RNA HOTTIP promotes breast cancer cell migration, invasiveness, and epithelial–mesenchymal transition via the Wnt–β-catenin signaling pathway

Abstract: Long noncoding RNA HOTTIP (HOXA transcript at the distal tip) has recently been reported to have a role in the proliferation of various cancer cells, yet its role in cell migration, invasiveness, and the EMT (epithelial–mesenchymal transition) in breast cancer and the potential mechanisms remain unknown. Breast cancer cell lines MDA-MB-231 and MDA-MB-468 were transfected with shRNA (short hairpin RNA) that specifically targeting HOTTIP. We observed a remarkable decrease in migration and invasiveness in these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In addition to the one report on a connection between HOTTIP and EMT in glioma, there are a few other reports connecting HOTTIP with EMT in some other cancers. Examples include the effect of HOTTIP on EMT in breast cancer ( 24 ), gastric cancer ( 25 ), osteosarcoma ( 26 ), ovarian cancer ( 27 ). Such EMT induction by HOTTIP has been linked to cisplatin resistance in gastric cancer ( 28 ), thus further validating HOTTIP mediated EMT in resistance against therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the one report on a connection between HOTTIP and EMT in glioma, there are a few other reports connecting HOTTIP with EMT in some other cancers. Examples include the effect of HOTTIP on EMT in breast cancer ( 24 ), gastric cancer ( 25 ), osteosarcoma ( 26 ), ovarian cancer ( 27 ). Such EMT induction by HOTTIP has been linked to cisplatin resistance in gastric cancer ( 28 ), thus further validating HOTTIP mediated EMT in resistance against therapies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HOTTIP expression is significantly increased in breast cancer tissues, compared to adjacent non-cancerous tissues. [24][25][26] We used the Kaplan-Meier plotter (http://www. kmplot.com) to investigate the prognostic significance of HOTTIP by defining upper tertile as cut-off, and found that patients with high HOTTIP expression displayed shorter overall survival (OS; P < .01, Figure 1A).…”
Section: Hottip Is Highly Up-regulated In Breast Cancer and Bcscsmentioning
confidence: 99%
“…However, HOTTIP-knockdown also reduced the expression of E-cadherin, another key marker of EMT, although there may not be an obvious regulatory association between miR-574-5p and E-cadherin. HOTTIP may affects the expression of E-cadherin through other mechanisms, such as the Wnt-β-catenin signaling pathway (17,24) or modifications by salinomycin (19) as reported in other types of cancer.…”
Section: Discssionmentioning
confidence: 89%
“…Multiple studies have suggested that HOTTIP acts as an oncogene in esophageal squamous cell carcinoma by inducing EMT via the HOTTIP-miR-30b-HOXA13 axis, in which HOXA13 is a downstream factor of HOTTIP that has been demonstrated to be directly regulated by HOTTIP (15,16). HOTTIP has also been reported to promote EMT in breast cancer and tongue squamous carcinoma through the ceRNA network or other mechanisms (17,18). Previous studies have suggested that HOTTIP and c-Myc may form a positive feedback regulatory loop in osteosarcoma, whereas salinomycin may reduce the development of EMT-mediated multidrug resistance by changing the expression of HOTTIP in gastric cancer cells (19,20).…”
Section: Discssionmentioning
confidence: 99%